Adaptive and service-oriented embedded system for information security applications. (January 2019) - Huang, Chun-Hsian; Chen, Huang-Yi; Tzeng, Yao-Ying; Li, Peng-Yi
Abstract: To provide a complete information protection mechanism, we propose an adaptive and service-oriented embedded system (ASOS) design. The access control policies are implemented as protection matrices and designed in hardware; thus, the information access method is specific and not generic, so that the risks of illegal access of information can be reduced. A layered and virtualizable design method is also introduced in the ASOS to enhance its scalability. Furthermore, the ASOS contains a system adaptation manager that can dynamically adapt its hardware functions to support various application requirements. Experiments show that compared to a pure software-based design, the ASOS can accelerate the access time by a factor of 8.75. Moreover, compared to a conventional embedded system design containing 13 hardware functions, the ASOS can reduce 26.42% of slice registers and 25.81% of slice LUTs in a Xilinx Virtex 6 XC6VLX240T FPGA.